Odpowiedź :
Odpowiedź:
a) 3x= - 8 /:3
x= - 8/3= - 2 i 2/3
spr... 3*(- 8/3) = -8 ( skracamy 3i 3 przez 3)
-8= - 8
L=P
b) -5a = - 15 /: 5
a= 3
spr... -5 *3= - 15
-15= - 15
L=P
c) 7g= -21 /:7
g= - 3
spr... 7*(-3) = -21
-21= - 21
L=P
d) 6y = - 20 /: 6
y= -20/6 = - 3 i 2/6
spr... 6* (-20/6)= -20 ( skr.. 6 i 6 przez 6)
- 20= - 20
L=P
e) 1/5 x= 7 /:1/5
x= 35
spr... 1/5 *35 =7 ( skr... 5 i 35 przez 5)
7=7
L=P
f) -2/3 j =4 /:2/3
j= 4 :(-2/3)= 4*3/2 ( skr... 4 i 2 przez 2)= - 2*3= -6
j=6
spr... -2/3 *(-6) = 4 ( skr.. 6 i 3 przez 3)
-2 * (-2)=4
4=4
L=P
Szczegółowe wyjaśnienie: